Targeting Mutated Plus Germline Epitopes Confers Pre-clinical Efficacy of an Instantly Formulated Cancer Nano-Vaccine - Mohsen, Mona O.; Vogel, Monique; Riether, Carsten; Muller, Julius; Salatino, Silvia; Ternette, Nicola; Gomes, Ariane C.; Cabral-Miranda, Gustavo; El-Turabi, Aadil; Ruedl, Christiane; Kundig, Thomas M.; Dermime, Said; et al. (Frontiers in Immunology, 2019)
Personalized cancer vaccines hold promises for future cancer therapy. Targeting neoantigens is perceived as more beneficial compared to germline, non-mutated antigens. However, it is a practical challenge to identify and vaccinate patients with neoantigens. Here we asked whether two neoantigens are sufficient, and whether the addition of germline antigens would enhance the therapeutic efficacy. We developed and used a personalized cancer nano-vaccine platform based on virus-like particles loaded with toll-like receptor ligands. We generated three sets of multi-target vaccines [MTV] to immunize against the aggressive B16F10 murine melanoma: One set based on germline epitopes [GL-MTV] identified by immunopeptidomics, another set based on mutated epitopes [Mutated-MTV] predicted by whole exome sequencing and a last set that combines both germline and mutated epitopes [Mix-MTV]. Our results demonstrate that both germline and mutated epitopes induced protection but the best therapeutic effect was achieved with the combination of both. Our platform is based on Cu-free click chemistry used for peptide-VLP coupling, thus enabling bedside production of a personalized cancer vaccine, ready for clinical translation.